2022-RA-1401-ESGO Comparison of ADNEXmodel, O-RADSand the combinedIOTA simple rules with simple rules risk assessment and simple rules with ADNEX model in discriminating between benign and malignant adnexalmasses. (20th October 2022) - Spagnol, Giulia; Xhindoli, Livia; Marchetti, Matteo; Bigardi, Sofia; Ciancia, Marianna; Bonaldo, Giulio; Saccardi, Carlo; Tozzi, Roberto; Noventa, Marco
Abstract : Introduction/Background: To compare the IOTA Assessment of Different NEoplasias in the adneXa (ADNEX) model, the Ovarian-Adnexal Reporting and Data System (O-RADS) and the combined IOTA Simple Rules (SR) with Simple Rules Risk (SRR) assessment and SR with ADNEX model in the preoperative discrimination of benign and malignant adnexal masses (AM). Methodology: We conducted a monocentric retrospective study performed between January-2018 to December-2021 which includes consecutive women with AM. Surgery with histology represented the reference standard. We classified the AM using the ADNEX model, O-RADS and SR in the same cohort of patients. When SR resulted 'inconclusive', we combined SR with SRR assessment and SR with ADNEX model. Sensitivity (SE), specificity (SP) and diagnostic accuracy (DA) were determined for each testing modality to compare the performance of ADNEX model, O-RADS, SR + SRR and SR + ADNEX model. Results: Of the 514 women, 400 (77.8%) had a benign ovarian tumor and 114 (22.2%) had a malignant tumor. The malignancy risk threshold was set at >10%. SE, SP and DA of the ADNEX model were 92, 1% (95%CI, 85, 5%-96, 3%), 88, 3% (95%CI, 84, 6%-91, 2%) and 89, 1% (86, 1%-91, 7%), respectively. SE, SP and DA of O-RADS were 93, 0% (95%CI, 86, 6%-96, 9%), 89, 3% (95%CI, 85, 8%-92, 1%) and 90.1% (95%CI, 87, 2–92, 5%), respectively. When we applied SR, 109 (21.2%) cases resulted inconclusive. SE, SP and DA of the SR + SRR assessment were 87, 7% (95%CI, 80, 3%-93, 1%), 91, 8% (95%CI, 88, 6%94, 3%) and 90, 9% (95%CI, 88, 0%-93, 2%), respectively. SE, SP and DA of the SR + ADNEX model were 90, 4% (95%CI, 83, 4%-95, 1%), 93, 3% (95%CI 90, 3%-95, 5%) and 92, 6% (90%-94, 7%), respectively. Conclusion: The ADNEX model and O-RADS had similar SE and higher SE than SR + SRR assessment and SR + ADNEX model in the preoperative discrimination of malignant and benign AM; SR + ADNEX model had higher DA than ADNEX model, O-RADS and SR + SRR assessment.